Oral Health Care Delivery for Children During COVID-19 Pandemic-A Retrospective Study - Avia Fux-Noy; Luna Mattar; Aviv Shmueli; Elinor Halperson; Diana Ram; Moti Moskovitz (Frontiers Media S.A., 2021)
Aim: COVID-19 outbreak and the lockdown period following was a very challenging time for pediatric dentistry. We aimed to find whether the characteristics of dental care provided to children at the Department of Pediatric Dentistry at Hadassah medical center, Jerusalem, Israel, differed between the periods, before COVID-19 outbreak, during the lockdown period and during the period that followed it.Materials and Methods: We retrospectively reviewed computerized records of patients who visited the pediatric dental clinic at three different periods: pre-lockdown period, lockdown period, and post-lockdown period.Results: Nine-hundred and forty-nine children were included in the study; most of them were healthy children between 3 and 6 years old. During lockdown, all scheduled appointments except for treatments under general anesthesia and deep sedation were canceled due to the government's restrictions; the frequency of treatments with non-pharmacological behavior management, general anesthesia or deep sedation was higher than in the previous or subsequent periods and the use of inhaled/conscious sedation was significantly lower. During lockdown most of the children were diagnosed with dentoalveolar abscess (32.3%), compared to 14 and 21% at the previous or subsequent periods, respectively (P < 0.001). Treatments combination during lockdown included more extractions, pulpectomies and pulp extirpation and less permanent restorations (P < 0.001). None of the staff members was infected with COVID-19 at the clinic during these periods. We concluded that dentists should be updated about Covid-19 modes of transmission and the recommended infection control measures in dental settings. Effective management protocols can help the dental staff to continue to provide efficient treatment and prevent Covid-19 contamination.